Refleksi Pemikiran M. Ibrahim Abu Rabi Dalam Pendekatan Integratif Interkonektif - Tashya Panji Nugraha (Pascasarjana IAIN Metro, 2017)
As a result of tragedy that occurred on September 11, 2001 to make Islam cornered and in the claims as a religion that is synonymous with violence. The phenomenon of terror and violence in the claims rooted in their religious texts. Some of the western states that violence is taught and derived from the Qur'an. Identification of the west against Islam to discourse to analyze the roots of the teachings of Islam accused which represents religious teachings or religious terrorist violence. Ibrahim M. Abu Rabi make this phenomenon as a momentum to conduct a review of hahekat Islamic thought. Abu Rabi doing three approaches in starting penelaahannya, starting with the historical development of Islamic modernisatiom, education in the Islamic world, and the contemporary elite and the religious revival in the Arab world. Approach to philosophy, theology critical, socio- historical, and anthropology to the study of Islam in intimated by Abu Rabi to bring Islam to the condition that advanced to accumulate in interconection integration way think. The concept of Islamic thought through a critical historical approach which is described by Abu Rabi in his work entitled Post September 11 Critical Assessment of Modern Islamic History is, when are reflected on an integration approach interconection which elaborated and initiated by M. Amin Abdullah showed that the reconceptualization of epistemology renewal of Islamic thought through an integrative approach undoubtedly interconective is needed to quell the violence at the phenomenon, and greatly required in religious plurality in Indonesia in particular.